2018
DOI: 10.1210/en.2018-00465
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Are Critical Factors in Ischemic Stroke Pathology

Abstract: Ischemic stroke is a devastating brain injury resulting in high mortality and substantial loss of function. Understanding the pathophysiology of ischemic stroke risk, mortality, and functional loss is critical to the development of new therapies. Age and sex have a complex and interactive effect on ischemic stroke risk and pathophysiology. Aging is the strongest nonmodifiable risk factor for ischemic stroke, and aged stroke patients have higher mortality and morbidity and poorer functional recovery than their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
171
4
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(203 citation statements)
references
References 172 publications
10
171
4
18
Order By: Relevance
“…IS is a complex syndrome triggered by cerebral embolism, with its major etiological subtypes being large artery stroke, cardioembolic stroke as well as the small vessel stroke [2]. Chronological age is one of critical factors in IS pathology but is not considered to be a causal factor [3]. This relationship might reflect the impact of biological aging, particularly, in regards to the accumulation of endothelial and vascular damage over time [4].…”
Section: Introductionmentioning
confidence: 99%
“…IS is a complex syndrome triggered by cerebral embolism, with its major etiological subtypes being large artery stroke, cardioembolic stroke as well as the small vessel stroke [2]. Chronological age is one of critical factors in IS pathology but is not considered to be a causal factor [3]. This relationship might reflect the impact of biological aging, particularly, in regards to the accumulation of endothelial and vascular damage over time [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the BCOS cannot be directly applied to ABI. While most strokes occur in older age (≥65 years) [ 20 ], most ABIs occur in adult age (16-44years) [ 21 ]. While the family caregivers of individuals with stroke are often in older age rather than middle-aged individuals (45-64years) [ 22 ], the family caregivers of individuals with ABI are often middle-aged or older.…”
Section: Introductionmentioning
confidence: 99%
“…These findings contradict the results of Roy-O'Reilly et al, which claimed that either age or LDL-C factors dominated the carotid stenosis. [14][15][16] The IPA capability of integrating individual factors with their probable cross-interaction improved the program convergence and yielded a high value of r 2 ¼ 0:9352.…”
Section: Resultsmentioning
confidence: 99%
“…Aging presented the dominant non-modifiable risk factor for ischemic stroke, which increased mortality/morbidity and inhibited functional recovery among older patients. 14 (2) LDL-C. Epidemiologists have reported that LDL-C level strongly promoted carotid stenosis in elderly patients with cerebral infarction. 15,16 (3) MAP.…”
Section: -4mentioning
confidence: 99%